Análise multivariada de leucograma e da resposta de fase aguda em equinos acometidos por síndrome cólica de origem natural ou experimental - Nogueira, Andressa Francisca Silva [UNESP] (2014)
The acute phase proteins are glycoproteins synthesized by hepatocytes and appear early in the bloodstream during inflammatory processes. The study aimed to identify, differentiate, measure, evaluate and compare the acute phase serum proteins in horses with naturally occurring colics and those undergoing experimental intestinal obstruction and correlate them with the leukon count in these animals. From the 27 adult horses studied 12 were treated in the Veterinary Hospital Governor Laudo Natel (FCAV / UNESP) from July 2010 to July 2013 for acute abdomen, survivors or not, and 15 animals were subjected to experimental small or large intestinal obstruction. Samples were obtained from whole blood with anticoagulant, to perform the WBC, and without anticoagulant to perform the SDS-PAGE electrophoretogram immediately before laparotomy (MO), after surgery (M1), and daily until the seventh day after surgery, except the sixth day (M2, M3, M4, M5, M6 and M7). For data analysis the multivariate statistical method with exploratory factor analysis was used. The horses with naturally occurringg colic showed intense inflammatory patterns that horses undergoing experimental intestinal obstruction. The horses undergoing experimental intestinal obstruction had also inflammatory obstruction established the model. The acute phase proteins had greater participation in the variability of the inflammatory response than the WBC and only when the influence of time in each group was evaluated there was a correlation between acute phase proteins and WBC. The acute phase protein alpha 1-acid glycoprotein, haptoglobin and ceruloplasmin were effective markers of the inflammatory response and its changes can be used as prognostic and time course indicators of acute abdomen in horses